Policy of KODIM 0501 Central Jakarta for Handling of the COVID-19 Pandemic in Central Jakarta - Arief Prayitno; Endang Sutrisno (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The Covid-19 pandemic has become an urgent issue, not only at the local level but also in the global realm of the world community. For this reason, all elements of society are actively and participatively involved in overcoming this health problem. The initial energy revolved around health issues but has now shifted to socio-economic problems and has even penetrated into the political and legal areas. Handling that must be carried out should be carried out in an active-participatory manner involving all components of the nation's interests, including in this case,Kodim 0501 was involved by the Jakarta Government in decidingthe spread of the Covid-19 outbreak in the Central Jakarta area. The task of the Kodim in dealing with the Covid-19 outbreak is the implementation of Military Operations Other than War (OMSP). This research aims to analyze the role of Kodim 0501/Central Jakarta and the Regional Government in dealing with the spread of the Covid-19 outbreak in the Central Jakarta area. Research findings prove that the handling of the spread of the Covid-19 outbreak in the Central Jakarta area is carried out with the Large-Scale Social Restrictions (PSBB) policy.Enforcement of Community Activity Restrictions (PPKM), and vaccinations. The role of Kodim 0501/Central Jakarta and the Regional Government in stopping the spread of the Covid-19 outbreak, is related to helping secure and supervising activities according to health protocols during vaccination activities, assisting with routine spraying of disinfectants, and helping distribute social assistance directly. The role of Kodim 0501/Central Jakarta and the Regional Government to stop the spread of the Covid-19 outbreak in the Central Jakarta area has been carried out very well.